Plant Responses to Vegetation Proximity: A Whole Life Avoiding Shade - Roig-Villanova, Irma; Martínez-García, Jaime F. (Frontiers in Plant Science, 2016)
In high density of vegetation, plants detect neighbors by perceiving changes in light quality through phytochrome photoreceptors. Close vegetation proximity might result in competition for resources, such as light. To face this challenge, plants have evolved two alternative strategies: to either tolerate or avoid shade. Shade-avoiding species generally adapt their development by inducing hypocotyl, stem and petiole elongation, apical dominance and flowering, and decreasing leaf expansion and yield, a set of responses collectively known as the shade avoidance syndrome (SAS). The SAS responses have been mostly studied at the seedling stage, centered on the increase of hypocotyl elongation. After compiling the main findings about SAS responses in seedlings, this review is focused on the response to shade at adult stages of development, such as petioles of adult leaves, and the little information available on the SAS responses in reproductive tissues. We discuss these responses based on the knowledge about the molecular mechanisms and components with a role in regulating the SAS response of the hypocotyls of Arabidopsis thaliana. The transcriptional networks involved in this process, as well as the communication among the tissues that perceive the shade and the ones that respond to this stimulus will also be briefly commented.